Andrew P. Debicki, Historia de la poesía española del siglo XX. Trad. A. P. Debicki. Gredos, Madrid, 1997; 342 pp. - Velásquez Guzmán, Mónica (El Colegio de México, 2000)
Se reseñó el libro: Historia de la poesía española del siglo XX.